Kinnow: Nutritionally Rich Functional Food for Value Addition - Zahra, Andleeb; Qaisrani, Tahira Batool; Ahmad, Matlob; Bilal, Talat (Journal of Agriculture and Veterinary Science, 2024)
Kinnow mandarin, a variety amongst citrus fruits is preferred for refreshing flavor pleasing aroma and bright color. It is rich in vitamins B complex and vitamin C, with remarkable minerals like calcium, phosphorus and other bioactive compounds. These compounds proved to have antioxidant, anti-inflammatory and antimicrobial activities. Pakistan is amongst of top kinnow producing countries on globe. Unfortunately, an ample quantity of its produce is wasted due to mishandling at post-harvest stage and lack of keeping facilities in under developing countries. This fruit is mainly processed to prepare beverages and juice-based products. One of the hindrances to its processing may be the presence of bittering compounds. Various de-bittering techniques can be opted to resolve this issue. Keeping in view its importance a lot of work has been done so far to prevent its losses. Kinnow fruit possesses a number of industrial and medical applications as well. Hence the processing is increasing in terms of techniques and products resulting in preparation of a number of value-added food products. The nutritional value of the kinnow prescribes its use in formulating a number of food products like ready to serve drinks, juices, squash, nectars, different blends, powders, candies, fermented products etc. This review covers information about kinnow production, harvesting, storage, post-harvest losses and their solutions globally. The article also highlights the nutritional importance, variety of products and techniques being applied in kinnow processing.
Keywords: Kinnow Mandarin; Value-added Products; Functional Ingredients; Nutrition